Hydration and durability of low-heat cementitious composites for dam concrete: Thermodynamic modeling and experiments - Zhang, Juntao; Lv, Tong (Frontiers in Materials, 2023)
To demonstrate the superiority of dam concrete, a systematic study was conducted to examine the durability of low-heat cementitious composite (LHCC) that is composed of Portland cement (PC), fly ash (FA), and MgO expansive additive (MEA) with PC as the reference group. Through GEMS software, XRD, SEM, and EDS, the difference mechanism in durability between the two cementitious materials was revealed from the perspectives of phase evolution and microstructural characteristics. Water at 40 °C was adopted for curing in the study to match the long-term temperature field inside the concrete dam. According to the results of the RCM, accelerated carbonation, and rapid freeze–thaw cycle experiments, LHCC outperforms PC in durability. The hydration process of LHCC is simulated by inputting the reaction degree of each phase calculated using the MPK model into the GEMS software. The thermodynamic model output shows that portlandite first increases and then decreases as LHCC hydration proceeds, and C-S-H and stratlingite are supplemented in the later stage, which reflects the high performance of FA involved in hydration. In addition, hydrotalcite that is capable of chloride ion adsorption is increasingly generated with the consumption of brucite. As is clearly shown in the SEM images, there are denser space grids formed by overlapping C-S-H in LHCC with almost no capillary pores. Meanwhile, when combined with the results of EDS, it is strongly demonstrated that the FA in LHCC can be hydrated to produce dense fibrous C-S-H in large amounts, providing a basis for the positive development of durability.